Pembuatan Direktori Pengrajin Tenun Pandai Sikek di Nagari Pandai Sikek, Kecamatan X Koto, Kabupaten Tanah Datar, Sumatera Barat - Ramandra, Yuli Atni; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper focuses on the manufacture of woven Clever entrepreneurs Sikek directory that can be used to determine enun Clever entrepreneurs Sikek. The purpose of this paper is to investigate the manufacture of woven Clever entrepreneurs directory Sikek X Koto subdistrict of Tanah Datar regency of West Sumatra. This writing method descriptive research. Data collection techniques are observation, interview, and literature. Data is collected on the whole shop craftsmen songket in Pandai Sikek X Koto subdistrict Tanah Datar. The results of this paper is that there are 17 stores weavers in Pandai Sikek X Koto subdistrict Tanah Datar which include named; Aisha Songket, Fatimah Sayuthi, Fortune / Dal Songket, Indah Karya, Limpapeh Gallery, Mayang Taurai, Namira Collection, Nan Sari Gallery, Nella Souvenir Shop, Mr. Datuk, Clever Sikek Art, Pusako Minang, Houses Songket, One Works, Sikumbang, Songket Bundo Maimbau and Craft Shop Smart Singkek. The handicrafts are marketed by these stores is Songket, embroidery, embroidered, Soevenir, Peci, Sulam Bayang, and mukena Kerancang.Keywords: Directory, weaving, Pandai Sikek.